Effects of mechanical vibration on root resorption in the rat molar induced by a heavy orthodontic force - Yeoh Ping Ping; Cheng Lam L.; Papadopoulou Alexandra K.; Darendeliler M. Ali (Sciendo, 2017)
Orthodontically-induced inflammatory root resorption (OIIRR) is an unwelcome side effect of orthodontic treatment. Mechanical vibration has been suggested as a preventative measure but evidence is limited. The aim of this study was to investigate whether whole body mechanical vibration has a positive influence on OIIRR.